Asparagine and Boric Acid Cause Allantoate Accumulation in Soybean Leaves by Inhibiting Manganese-Dependent Allantoate Amidohydrolase - Lukaszewski, Krystyna M. (1992)
Our previous work demonstrated substantial accumulation of allantoate in leaf tissue of nodulated soybeans (Glycine max L. Merr., cv Williams) in response to nitrogen fertilization. Research was continued to determine the effect of nitrate and asparagine on ureide assimilation in soybean leaves. Stem infusion of asparagine into ureide-transporting soybeans resulted in a significant increase in allantoate concentration in leaf tissue. Accumulation of allantoate was also observed when asparagine was supplied in the presence of allopurinol, an inhibitor of xanthine dehydrogenase in the pathway of ureide biosynthesis. In vitro, asparagine was found to have an inhibitory effect on the activity of allantoate amidohydrolase, a Mn(2+)-dependent enzyme catalyzing allantoate breakdown in soybean leaves. The inhibition was partially overcome by supplemental Mn(2+) in enzyme assays. Another inhibitor of allantoate amidohydrolase, boric acid, applied foliarly on field-grown nodulated soybeans, caused up to a 10-fold increase in allantoate content of leaf tissue. Accumulation of allantoate in response to boric acid was either eliminated or greatly reduced in plants presprayed with Mn(2+). We conclude that elevated levels of allantoate in leaves of ureide-transporting soybeans fertilized with ammonium nitrate result from inhibition of allantoate degradation by asparagine and that Mn(2+) is a critical factor in this inhibition. Furthermore, our studies with asparagine and boric acid indicate that availability of Mn(2+) has a direct effect on ureide catabolism in soybean.